2009
DOI: 10.1038/leu.2009.183
|View full text |Cite
|
Sign up to set email alerts
|

High dose ara-C in the treatment of newly diagnosed acute promyelocytic leukemia: long-term results of the German AMLCG

Abstract: The objective of this study for newly diagnosed acute promyelocytic Leukemia (APL) was to evaluate the efficacy of an intensified double induction chemotherapy including high dose ara-C (HD) and all-trans retinoic acid (ATRA) followed by consolidation and 3 years maintenance therapy. In contrast to APL studies stratifying therapy according to pretreatment white blood cell (WBC) count o and X10 Â 10 9 /l (low/intermediate and high risk according to the Sanz score), our patients received uniform therapy. From 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
69
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(78 citation statements)
references
References 36 publications
8
69
0
1
Order By: Relevance
“…All patients received all-trans retinoic acid in combination with intensive chemotherapy according to standard study protocols. 1,5,17 This cohort is completely independent of a previously published one. 11 All patients gave informed consent to the use of laboratory data for research studies.…”
Section: Patientssupporting
confidence: 49%
See 2 more Smart Citations
“…All patients received all-trans retinoic acid in combination with intensive chemotherapy according to standard study protocols. 1,5,17 This cohort is completely independent of a previously published one. 11 All patients gave informed consent to the use of laboratory data for research studies.…”
Section: Patientssupporting
confidence: 49%
“…[6][7] Lengfelder et al observed no significant differences in survival outcomes and relapse incidence in 142 APL patients (who all received cytarabine within their induction and consolidation protocols) when they were separated according to a WBC threshold of 10¥10 9 /L . 5 The most suitable parameters for risk stratification in APL are, therefore, still under debate. It was discussed whether patients with the French-American-British (FAB) subtype M3v might have higher rates of early death because of hemorrhagic complications when compared to patients with the classical FAB M3 morphology, [8][9] but Tallman et al found that outcomes of patients with the two FAB subtypes did not differ significantly when adjustment for WBC counts or relapse risk scores was made.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5][8][9][10] Recently, Jacomo et al reported an ED rate of 32% in a study of APL patients at 12 Brazilian institutions receiving treatment with ATRA and anthracyclines. Hemorrhages, caused by disseminated intravascular coagulation, hypercoagulability, fibrinolysis, proteolysis and thrombocytopenia, constitute the major cause of death with the central nervous system (CNS) being the most common site of bleeding.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16] These protocols included the AIDA 2000 of the Italian GIMEMA study group, 12 the PETHEMA LPA2005, 13 and the PETHEMA LPA 99, 14 UK MRC AML15 15 and the German AMLCG. 16 All protocols received approval from the corresponding IRB and/or ethical committees. Patients were enrolled in the respective trials prospectively and were treated accordingly after signing informed consent.…”
mentioning
confidence: 99%